Linkages of Leaves Moisture of Medical Plant (Senecio L.) and Elevation in Shan County - Liao, Bing-Hua (Journal of Drug Delivery and Therapeutics, 2021)
A key plant species (Senecio L.) not only is a vital multilevel functional medicinal material of indications of respiratory tract infections, tonsillitis, pharyngitis, pneumonia, conjunctivitis, enteritis, dysentery, but also it is a widely distributed wide plant species. This plant species is widely distributed elevation from 500m to 1500m in six landscapesin Shan County of China. However, understanding dynamics of leaves moisture of theplants is difficult along elevation. Herein showed that linkages between leaves moisture of the species and elevation is a significant positive connection from 500m to 1000m(P